The bubble bursts for cavitation in natural rivers: laboratory experiments reveal minor role in bedrock erosion. Issue 9 (31st January 2017) - Carling, Paul A.; Perillo, Mauricio; Best, Jim; Garcia, Marcelo H.
Abstract: The erosion of rock‐bedded channels generally is considered a slow process caused mainly by abrasion due to bedload or suspended sediments, but the mechanisms of rapid erosion remain unclear. Cavitation is a clear‐fluid erosive process, well known for its effect on engineering structures, when water vapour bubbles collapse and the resultant pressure shocks erode the boundary. However, although the occurrence of cavitation erosion in natural watercourses has long been a matter of debate, as yet there are no incontrovertible examples of cavitation damage to natural river beds. Using flume experiments, we show for the first time that only weakly‐cavitating clear‐water flows can occur for the range of flow velocities observed in rivers, and these do not erode medium‐hardness rocks after 68 hours. During this time period, only a very soft rock featured erosional marks due to dissolution. Thus, our results cast significant doubt on the likelihood of identifying cavitation damage in most rivers, and provide pointers to those river systems that might be investigated further to identify cavitation erosion. Copyright © 2016 John Wiley & Sons, Ltd.